2017
DOI: 10.1101/212456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Fluid Membrane determines Mechanics of Red Blood Cell Extracellular Vesicles and is Softened in Hereditary Spherocytosis

Abstract: was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…One striking observation in our study is the similarity in the mechanics of vesicles from different cells and origins, as well as isolation methods, blood donors, and experimentalists performing the vesicle isolation. We find that bending modulus values obtained here for RT incubated RBC are very comparable to those we previously measured in a different set of experiments with vesicles produced at similar conditions of RT 20 h incubation, [16] demonstrating again the robustness of our method.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One striking observation in our study is the similarity in the mechanics of vesicles from different cells and origins, as well as isolation methods, blood donors, and experimentalists performing the vesicle isolation. We find that bending modulus values obtained here for RT incubated RBC are very comparable to those we previously measured in a different set of experiments with vesicles produced at similar conditions of RT 20 h incubation, [16] demonstrating again the robustness of our method.…”
Section: Discussionsupporting
confidence: 87%
“…Very few previous pioneering studies addressed the importance of mechanical properties of extracellular vesicles and so far the pressurization of vesicles due to surface interactions has not been taken into account. Our recently developed approach does take pressurization into account. It allows reliable comparison of different vesicle populations, as we are able to estimate the bending modulus of the vesicles, an intrinsic material property that is independent of the measuring conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of proteins on the membrane mechanics has been investigated in various studies, some of which reported a significant increase in bending modulus of vesicles 50,51 , while others have shown either a neutral effect 52 or a decrease in the membrane stiffness. [53][54][55][56] Generally speaking, short peptides usually decrease the rigidity (stiffness) of the membrane 54 , while the effect of larger membrane proteins could be either neutral 52 or decreasing. 53,55 The reason for this is the hydrophobic mismatch due to the differences in the thickness of hydrophobic chain of the lipid molecule and the length of the hydrophobic surface of the protein 57 that causes a local bilayer thinning in the case of a short peptide.…”
Section: Effect Of Other Moleculesmentioning
confidence: 99%
“…[53][54][55][56] Generally speaking, short peptides usually decrease the rigidity (stiffness) of the membrane 54 , while the effect of larger membrane proteins could be either neutral 52 or decreasing. 53,55 The reason for this is the hydrophobic mismatch due to the differences in the thickness of hydrophobic chain of the lipid molecule and the length of the hydrophobic surface of the protein 57 that causes a local bilayer thinning in the case of a short peptide. The effect of proteins is discussed in more details in Chapter 4. mineral processing and biological analysis.…”
Section: Effect Of Other Moleculesmentioning
confidence: 99%
See 1 more Smart Citation